2023
DOI: 10.1097/mbc.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen reflects severity and predicts outcomes in patients with sepsis and septic shock

Abstract: The study investigates the diagnostic and prognostic value of fibrinogen and the albumin-to-fibrinogen-ratio (AFR) in patients with sepsis and septic shock. Limited data regarding the prognostic value of fibrinogen and AFR during the course of sepsis or septic shock are available. Consecutive patients with sepsis and septic shock from 2019 to 2021 were included monocentrically. Blood samples were retrieved from the day of disease onset (day 1), as well as on day 2 and 3. Firstly, the diagnostic value of fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…24–26 Elevated fibrinogen levels are an independent risk factor for death after sepsis, suggesting that elevated fibrinogen levels may have prognostic value for sepsis. 27,28 The results of this current study showed that patients with extremely severe burns and high fibrinogen levels had nearly a two-fold greater risk of developing sepsis than those with low fibrinogen levels. However, the pathological mechanism by which elevated fibrinogen levels increase the risk for sepsis remains unclear.…”
Section: Discussionmentioning
confidence: 59%
“…24–26 Elevated fibrinogen levels are an independent risk factor for death after sepsis, suggesting that elevated fibrinogen levels may have prognostic value for sepsis. 27,28 The results of this current study showed that patients with extremely severe burns and high fibrinogen levels had nearly a two-fold greater risk of developing sepsis than those with low fibrinogen levels. However, the pathological mechanism by which elevated fibrinogen levels increase the risk for sepsis remains unclear.…”
Section: Discussionmentioning
confidence: 59%